The human cost of disasters: an overview of the last 20 years (2000-2019) - UNDRR (UN Office for Disaster Risk Reduction, 2020)
UNDRR report published to mark the International Day for Disaster Risk Reduction on October 13, 2020, confirms how extreme weather events have come to dominate the disaster landscape in the 21st century.
Keywords: Ouvrage_Collectif_Numéro1

Global assessment report on disaster risk reduction 2019 - United Nations Office for Disaster Risk Reduction (UNDRR) (United Nations Office for Disaster Risk Reduction (UNDRR), 2019)
The 2019 Global Assessment Report on Disaster Risk Reduction (GAR) is informed by the latest data – including Sendai Framework target reporting by countries using the Sendai Framework Monitor
Keywords: Ouvrage_Collectif_Numéro1